Data from: Bacterial epibiont communities of panmictic Antarctic krill are spatially structured - Clarke, Laurence; Suter, Leonie; King, Rob; Bissett, Andrew; Bestley, Sophie; Deagle, Bruce (Zenodo, 2021)
Antarctic krill ( Euphausia superba ) are amongst the most abundant animals on Earth, with a circumpolar distribution in the Southern Ocean. Genetic and genomic studies have failed to detect any population structure for the species, suggesting a single panmictic population. However, the hyper-abundance of krill slows the rate of genetic differentiation, masking potential underlying structure. Here we use high-throughput sequencing of bacterial 16S rRNA genes to show that krill bacterial epibiont communities exhibit spatial structuring, driven mainly by distance rather than environmental factors, especially for strongly krill-associated bacteria. Estimating the ecological processes driving bacterial community turnover indicated this was driven by bacterial dispersal limitation increasing with geographic distance. Furthermore, divergent epibiont communities generated from a single krill swarm split between aquarium tanks under near identical conditions suggests physical isolation in itself can cause krill-associated bacterial communities to diverge. Our findings show that Antarctic krill-associated bacterial communities are geographically structured, in direct contrast with the lack of structure observed for krill genetic and genomic data.